Examining the role of working memory resources in following spoken instructions. Issue 2 (17th February 2016) - Yang, Tian-xiao; Allen, Richard J.; Gathercole, Susan E.
ABSTRACT: This study investigated the involvement of working memory (WM) in following spoken instructions using concurrent tasks designed to disrupt components of the Baddeley and Hitch WM model [Baddeley, A. D., & Hitch, G. J. (1974). Working memory. In G. H. Bower (Ed.), The psychology of learning and motivation: Advances in research and theory (Vol. 8, pp. 47–89). New York, NY: Academic Press]. In each of three experiments, participants were presented with sequences of instructions to be either verbally repeated or physically performed using relevant objects. Backward counting, articulatory suppression, and eye closure during instruction encoding all disrupted recall, and also impaired recall of the linkage between movements and objects. Recall of actions was more accurate when they were physically enacted than repeated verbally, an advantage that was not affected by concurrent tasks. These findings indicate that aspects of the recall of spoken instructions including the binding of constituent movements to objects draw on multiple WM resources. The benefits of physical enactment of the instructed sequence do not appear to depend on the components of WM investigated in these studies.